The Supreme Court in a Pluralistic World: Four Readings of a Reference - Glover, Kate (McGill Law Journal / Revue de droit de McGill, 2015)
Dominant narratives about the institutional life of the Supreme Court of Canada pay too little attention to the empirical and theoretical insights of legal pluralism. They do not say enough about the Court’s place in a world in which the nature and experience of law are often understood without reference to state sources or institutions. As a result, the prevailing narratives do not speak to many social realities, fail to build on rich pluralist critiques of the Court’s jurisprudence, and disregard the aims and promise of doing legal theory.Relying on the Reference Re Senate Reform as a case study, this article points to shortcomings of contemporary understandings of the Court and proposes a way to overcome them. Part I presents four readings of the Supreme Court’s opinion in the Reference. Each focuses on a different dimension of the case—the doctrinal, the metaphorical, the institutional and the contextual. The readings are an invitation to notice the assumptions embedded in interpretations of the Reference and to explore the larger narratives of which they are a part. Part II takes up that invitation. It shows that the dominant narratives often reflect state-centric traditions of legal theory and impede inquiries into the Court’s place in a legally and institutionally plural world. It then presents a research agenda that maps a route toward filling this gap. Drawing on lessons of legal pluralism, the agenda encourages us to confront what we think we know—and what we tend to ignore—about the morality of the Court’s institutional design, about the Court’s place in Canada’s constitutional imagination, and about the significance of the Court in light of the myriad ways in which we access and pursue justice.